UNLAWFUL ARREST AND UNLAWFUL DETENTION: SEPARATE GROUNDS OF ACTION AND PUNITIVE DAMAGES Mvu v Minister of Safety and Security 2009 6 SA 82 (GSJ) - J Neethling; JM Potgieter (Obiter, 2021)
In Mvu v Minister of Safety and Security the plaintiff, an inspector in the South African Police Service was arrested without a warrant for malicious damage to property (his 15-year old daughters’ cellphones). It transpired that the plaintiff, while on police business in Gauteng, visited his daughters. He became enraged when he discovered that they had received cellphones by way of a “love relationship”, whereupon he took the cellphones and threw them to the ground, seriously damaging them. The daughters went to a police station and laid a charge against the plaintiff for malicious damage to property. The police officer seized with the matter telephoned the plaintiff who immediately travelled to meet him. Upon arrival he arrested the plaintiff and imprisoned him overnight with six other men and set him free the following afternoon on warning. When the matter eventually came to court, the plaintiff was discharged at the end of the state’s case.